Basic Study on Evaluation of Earphone Hearing Loss - Audiogram Database for Ear Age Estimation - - Hirotoshi Hishida; Tomoki Watanabe; Yamato Fujii; Yasuhiro Hishida; Keiko Hishida (Journal of Systemics, Cybernetics and Informatics)

(untitled)
Audiograms indicate expected ear age when used in studies that address the prevention of deafness resulting from earphone use. So far, the authors have collected data from Japan and other countries, statistically integrated them, and evaluated errors. While a Caucasian population was sampled in a previous study, a Japanese sample was considered in the present study. The present study refers to the simplest modeling example of an audiogram, which is confirmed to be in good agreement with the actual situation. The gender gap of Japanese people was smaller than that of Caucasians. Furthermore, Japanese and Caucasian females were less likely to have deafness than males, and hearing capabilities of males varied more than that of females. The hearing of young people falls near 3000 Hz as a result of the integration, but it is considered that the graph around the region should be interpolated smoothly. Improving the modeling accuracy would let us understand various things.